THE INFLUENCE OF COMPENSATION JUSTICE FACTORS, GOVERNMENT INTERNAL CONTROL SYSTEMS, AND ORGANIZATIONAL ETHICS ON CORRUPTION IN THE GOVERNMENT SECTOR WITH LAW ENFORCEMENT AS A MODERATING VARIABLE - Alexander Mychael Silaban; Haryono Umar (Jurnal Magister Akuntansi Trisakti, 2023)
This study aims to examine The Influence of Compensation Justice, Government Internal Control Systems, and Organizational Ethics Factors, Against Corruption in The Government Sector with Law Enforcement as a Moderating Variable. The object of research is the work unit within the Human Resources Development Agency of Transportation by the number of respondents as many as 101 people were deliberately selected employees who handle financing activities, budgeting activities, assets management, and human resource departments. The type of data used is primary data and using multiple regression analysis was processed using SPSS 26.0. This study was designed using descriptive causal analysis and test the hypothesis by taking a test unit at the Human Resources Development Agency of Transportation. Data obtained through questionnaires, the sample is selected with the specific purpose (purposive sampling) and the data were analyzed using multiple linear regression. The results showed that the Organizational Ethics, and Government Internal Control System moderated by Law Enforcement give effect to Corruption, while the Compensation Justice, Government Internal Control System and Compensation Justice, Organizational Ethics moderated by Law Enforcement do not affect the Corruption. Based on the results, the training, education,  and develop the code of ethics can improve the quality of human resources of The Government Internal Supervisory Apparatus.